2019
DOI: 10.1186/s12610-018-0081-3
|View full text |Cite
|
Sign up to set email alerts
|

Penile Lymphangioma: review of the literature with a case presentation

Abstract: BackgroundPenile lymphangiomas are rare manifestations of lymphangiomas or lymphatic malformations which are more commonly found in the head or neck region of the body. Lymphangiomas are further categorized as lymphangioma circumscriptum, cavernous lymphangioma, cystic hygroma, or acquired lymphangiomas (also known as lymphangiectasia), based on their depth and etiology.ResultsA literature review revealed only 30 cases of penile lymphangioma between 1947 and March 30, 2018. Several causes were attributed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 22 publications
0
26
1
Order By: Relevance
“…Acquired cases appear to develop most frequently after infections of lymphatic channels, irradiation, or surgery [1]. In a recent review of the literature, Macki et al [2] reported only 8 cases of LC between 1947 and April 2018. Five of these were congenital and 3 were related to lichen planus, recurrent cellulitis, and ulcerative colitis.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Acquired cases appear to develop most frequently after infections of lymphatic channels, irradiation, or surgery [1]. In a recent review of the literature, Macki et al [2] reported only 8 cases of LC between 1947 and April 2018. Five of these were congenital and 3 were related to lichen planus, recurrent cellulitis, and ulcerative colitis.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Males of infertile couples, defined according to the WHO [ 73 ], were investigated in nine studies [ 22 , 47 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. IDF&AHA/NHLBI criteria were applied in three studies [ 47 , 60 , 61 ], whereas the AHA/NHLBI definition was used in one report [ 62 ], and NCEP-ATPIII criteria were used in five reports [ 22 , 56 , 57 , 58 , 59 ]. Ferlin et al [ 22 ] also showed a significantly higher frequency of MetS in men with a low sperm count compared to those with a normal one (8.1% vs. 6.6%, respectively).…”
Section: Mets Prevalence In Infertile and Fertile Menmentioning
confidence: 99%
“…LC might be either congenital or acquired, and is predominantly located on the trunk, buttock, axillary region, or thighs. 1 Penile LC is rare. We report a case of acquired LC in a patient with high-grade penile intraepithelial neoplasia (PeIN).…”
mentioning
confidence: 99%
“…5 Most cases of acquired LC have been reported in association with predisposing tissue alteration such as trauma, surgery, radiation exposure, chronic inflammation (e.g., hidradenitis suppurativa, inflammatory bowel disease, or recurrent cellulitis), or cancer. 1,57 Such alternations seem to hinder the subcutaneous lymphatic cisterns from completely draining into the general lymphatic system. 6 The association of acquired LC and penile HPV-induced lesions has been reported only once in a 24-year-old man with multiple genital HPV6-positive condylomata acuminata.…”
mentioning
confidence: 99%
See 1 more Smart Citation